Design of an Expert System to Enhance Learners' Critical Thinking in a Task-based Online Discussion - Nantha Kumar , Subramaniam; Abdullah Mohd Zin; Sufian Idris (2010)
Teaching-Learning Process and Technology components in the principles of effectiveness for serving adult learners are the most important elements in empowering learners to be the co-creators of knowledge. There are various ways to blend teaching-learning process and technology components to enrich educational experience for the adult learners such as multimedia learning systems and learning objects. In this paper, we will discuss of how we have integrated collaborative learning pedagogy and asynchronous discussion board (forum) in order to design an expert system with the objective of promoting critical thinking aspects in a small group learning. (Authors' abstract)